An investigation on the income accruing to sorghum-rice enterprise in response to the most profitable mixture combination for adoption by farmers - Bayo Paul; Bolanle Akiolu; Yemi Philips (African Journal of Environmental Economics and Management, 2015)
Multiple cropping offers farmers the opportunity to engage nature’s principles of diversity on farms. A field trial that was conducted in Nigeria, investigated the yield and economic returns that accrued to sorghum and rice; in sorghum – rice intercrop as affected by rice inclusion in the proportions: 1:1, 1:2, 1:3 and 1:4, respectively for sorghum and rice. Analysis of yield data for both cropping seasons revealed significant influence of sorghum – rice intercrop on grain yields of sorghum and rice in mixtures. Observed average sorghum yield in sole plot was 1712.39 kg ha-1, which was progressively significantly decreased with progressive inclusion of rice rows from 1050.58 kg ha-1 (38.65 % yield reduction) in 1:1 sorghum – rice mixture to 300.35 kg ha-1 (82.46% yield reduction) in 1:4 sorghum – rice mixture; while grain yields of sorghum decreased with progressive rice inclusion, grain yields of rice increased per hectare with progressive increase in rice rows from 1:1 to 1:4. Considering the economic implication of intercropping sorghum with rice, income that accrued to sole crops was significantly reduced with intercropping. While all the crop combinations investigated performed better than sole cropped sorghum (in terms of revenue generation), sole rice performed better than all the intercrops. The implication of this observation is that while sorghum is better intercropped with rice to improve revenue generation, rice is best as sole crop. In conclusion, in sorghum – rice intercrop, intercropping at 1:4 is recommended as this mixture gave best intercrop result in respect to monetary return relative to other mixtures.